Marx and Keynes: From exploitation to employment - Fritz Helmedag (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2019)
Marx's and Keynes's analyses of capitalism complement each other well. In a rather general model including the public sector and international trade it is shown that the labour theory of value provides a sound foundation to reveal the factors influencing employment. Workers buy "necessaries" out of their disposable wages from an integrated basic sector, whereas the "luxury" department's revenues spring from other sources of income. In order to maximize profits, the wage good industry controls the level of unit labour costs. After all, effective demand governs the volume of work. On this basis, implications for economic policy are outlined.
Keywords: E11; E12; E24; 330; Employment; Marx; Keynes; Surplus value